U-Statistic for Multivariate Stable Distributions - Mahdi Teimouri; Saeid Rezakhah; Adel Mohammadpour (Journal of Probability and Statistics)
A U-statistic for the tail index of a multivariate stable random vector is given as an extension of the univariate case introduced by Fan (2006). Asymptotic normality and consistency of the proposed U-statistic for the tail index are proved theoretically. The proposed estimator is used to estimate the spectral measure. The performance of both introduced tail index and spectral measure estimators is compared with the known estimators by comprehensive simulations and real datasets.